Dephosphorisation of ferromanganese alloy using rare earth oxide-containing slags. (2nd October 2018) - Xi, Xiaojun; Luo, Diqiang; Cai, Xina; Lai, Chaobin
ABSTRACT: The phosphates of rare earth (RE) metals are highly stable in natural environment, and RE oxides have higher optical basicity than CaO and BaO. Therefore, the thermodynamic conditions for dephosphorisation using RE oxide-containing slags are expected to be favourable. Factors influencing the efficiency and Mn loss during the dephosphorisation of ferromanganese using RE oxide-containing slags were studied. An increase in the dephosphorisation temperature up to 1673 K (1400°C) is beneficial to the process and decreases Mn loss, and the maximum degree of dephosphorisation for slags containing 6 wt% RE oxides are 47.44 and 50.85%, corresponding to the minimum values of Mn loss are 1.64 and 1.35% at 1673 K (1400°C); further temperature increases would deteriorate the dephosphorisation efficiency and lead to an obvious increase in Mn loss. An increase in the quantity of pre-melted slags, and of their RE oxide content, improves the dephosphorisation efficiency but inevitably leads to a more pronounced Mn loss. It was also found that an increase in Si contents above 0.25 wt% in the ferromanganese alloys not only deteriorates the dephosphorisation efficiency but also increases the Mn loss; and the dephosphorisation efficiency decreases to almost zero when the silicon content increases up to 0.62 wt%.